Low cost technology applied to thermometry of grains - Ferrasa, Marcelo; Biaggioni, Marco Antonio Martin [UNESP]; Canteri, Marcelo Giovaneti (My University, 2009)
Modern agriculture demands investments in technology that allows the farmers to improve productivity and quality of their products, aiming to establish themselves in a competitive market. However, the high costs of acquiring and maintaining such technology may be an inhibiting factor to its spread and acceptance, mainly to a large number of small grain Brazilian farmers, who need low cost innovative technological solutions, suitable for their financial reality. Starting from this premise, this paper presents the development of a low cost prototype for monitoring the temperature and humidity of grains stored in silos, and the economic implications of cost/benefit ratio of innovative applications of low cost technology in the process of thermometry of grains. The prototype was made of two electronic units, one for acquisition and another one for data reception, as well as software, which offered the farmers more precise information for the control of aeration. The data communication between the electronic units and the software was reliable and both were developed using low cost electronic components and free software tools. The developed system was considered as potentially viable to small grain Brazilian farmers; it can be used in any type of small silos. It provided reduction of costs of installation and maintenance and also offered an easy expansion system; besides the low cost of development when compared to similar products available in the Brazilian market.
Keywords: Electronic; Silo; Small farmers; Software; Competitive markets; Cost/benefit ratio; Data reception; Data-communication; Economic implications; Electronic units; Free software; High costs; Inhibiting factors; Low cost technology; Low costs; Low-cost electronics; Small grains; Technological solution; Agriculture; Computer software maintenance; Costs; Grain (agricultural product); Productivity; Technology; Temperature sensors; Thermometers; Computer software